Portrayal of Shiva as Natesha or Nataraja on the Uttaranga - Temples of India Project Team (Jio Institute, 2024)
The captivating portrayal of Shiva as Natesha or Nataraja stands out on the uttaranga (entablature) above the lintel of the garbhagriha (sanctum sanctorum). It is one of the most exquisite sculptures in the temple. The depiction captures Shiva engaged in a dance to the rhythm of a drum skillfully played by the drummer depicted at the base. Shiva is not alone; Nandi accompanies him, seated at the lower left. Shiva's stance features his left foot on the ground while his right foot is elevated and pointed inward. In his upper arms, he holds a sarpa (snake), while his other arms grasp a damru (hourglass-shaped drum), khatvanga (staff with a skull), a bowl, a trishula (trident), and a kamandalu (water carrier or pot).